Filling the Gap: A Feasibility Study of a COPD-Specific Breathlessness Service - Kris Mooren; Danielle Wester; Huib Kerstjens; Erik Bergkamp; Anna Spathis; Yvonne Engels (COPD, 2022)
Refractory breathlessness is a devastating symptom in chronic obstructive pulmonary disease (COPD). Symptom-focused breathlessness services, involving palliative care teams, offer individualized support but are not yet widely available for people with nonmalignant disease among which COPD. Our primary aim was to demonstrate the feasibility of setting up a breathlessness service specifically for COPD patients within a respiratory outpatient clinic. Our secondary aims were to assess how many sessions patients need to complete the intervention; to obtain an indication of effect size (on the Chronic Respiratory Questionnaire (CRQ), subset mastery domain); and to evaluate patient and professional satisfaction. We conducted a non-randomized single-center feasibility study. Participants had COPD and refractory breathlessness. During at least one session with a respiratory nurse and a pulmonologist, and one session with a physiotherapist, patients learned non-pharmacological interventions to manage breathlessness. Of 34 screened patients, 19 were included. All completed the intervention. A median of two clinical visits and two telephone calls were needed to complete the intervention. The mean improvement of 1.55 in CRQ, mastery domain, significantly exceeded the clinically important difference of 0.5. The service was rated as excellent by the eight patients who completed the survey. The health professional team gave positive feedback on the experience of delivering the intervention. Delivery of a breathlessness service for COPD outpatients with refractory breathlessness appears feasible, easy to implement in a respiratory outpatient clinic, and has the potential to be effective. A randomized controlled clinical trial is needed to test effectiveness and cost-effectiveness in this context.